Evolution of ritual from antiquity to modern times - A. A. Nivnya (Granì, 2014)
This article illustrates transformation of ritual in different types of society. The author studies ritual models of behavior in the context of traditional culture, Christian religion as well as modern society. There is substantiated the impossibility for society to function without ritual scenarios. There is is investigated the role of ritual in traditional society. Ritual is interpreted as the only possible way of experiencing critical situations, transition periods and calendar lifecycles. On the example of individual socialization there is described function of conversion of natural in cultural through ritual. The author proves the ability of ritual to satisfy human needs in creation, ordering of the world and belonging to the divine. Ritual is also considered as a compulsory condition of succession of generations and strengthening ties inside the community. There is described the existence of ritual within the Christian religion. The author analyzes the origins of some traditional Christian holidays. In particular, the cosmogonic motifs in the Christmas cult are explained by subconscious need for maintaining world order and by the repeatability of the time cycles. There are proved initiation function of the rites of baptism and wedding. Focuses are made on the traditional ritual based on Christian rites designed to attach a believer to divinity. The author asserts the need of individual in the collective experience and symbolic actions. On the example of the celebration of «New Year» the author substantiates the necessity of  individual in modern times in the creation and ordering of the world. In the article the initiation burden of school graduation as well as modern wedding and maternity rites are analyzed. The author describes the way ritual maintains succession of generations and provides team building.